If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 + -2k = 14 Solving 22 + -2k = 14 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + -2k = 14 + -22 Combine like terms: 22 + -22 = 0 0 + -2k = 14 + -22 -2k = 14 + -22 Combine like terms: 14 + -22 = -8 -2k = -8 Divide each side by '-2'. k = 4 Simplifying k = 4
| 5.4=-logx | | -6(2-3x)-3=-15+2x | | (-3)*(-3)*(-3)+x=10x | | p/4-1=3 | | 4.7x+3.8=13.2l | | -2v+5v=-12 | | 445.53=.71x | | d/3-6=-2 | | X/8=21/14 | | x/4-9=-11 | | 5n-5=5n+10 | | 2/5*25=10 | | 4x+6y=4200 | | -11x=17 | | 2x-66=12 | | 7d+3=94 | | -9=-2v+5 | | 1/3xyz=p | | h/4-6=-1 | | 22-5p=57 | | q/8-1=2 | | 8x+4=92 | | 4x-6-2x=4 | | Q-1/21/2 | | -5+2m=25 | | 5=n/2-5 | | 6+6d=54 | | 8x-9=143 | | z/3-1=1 | | 5x-4+6x-9-4=2+2x+7 | | -2+10n=78 | | 2x+3-7(x-1)=2(x-55)+5x |